Evaluation of plant-based oils for production of offset printing ink - OKTAV, MEHMET (My University, 2022)
The oils and solvents are the main components of the printing ink, and the chemical composition of the ink could be harmful or toxic to human health and the environment. Therefore, there is an increasing demand to develop inks containing green, biobased, sustainable, and renewable raw materials instead of petrochemical substances. In this study, flaxseed oil (FO), pomegranate seed oil, plum kernel oil (PKO), and grape seed oil (GSO) were selected to produce offset printing inks. Pinus pinaster (P. pinaster) resin was also used in the formulation of inks to examine the effects of natural resin on ink together with vegetable oils. The phenolic content was analyzed for the resin and oils to figure out their potential antioxidant and bioactive characteristics. Optical and rheological tests were applied to evaluate the printability of the inks. L*a*b*, Delta E, density, and gloss tests were performed for optical evaluation. The viscosity, tack, and rub resistance tests were applied to perform rheological analysis. The biobased, environmental friendly, and self-drying (cold set) offset printing inks were obtained using natural pine resin and three different plant-based oils FO, PKO, and GSO. The printability analysis of the inks figured out the potential usage of plant-based oils in the offset printing ink formulation.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Kimya; Diğer; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Chemistry; Other; Natural Sciences; Engineering and Technology; KİMYA, UYGULAMALI; Temel Bilimler (SCI); GIDA BİLİMİ VE TEKNOLOJİSİ; Tarım Bilimleri; Tarım ve Çevre Bilimleri (AGE); CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); FOOD SCIENCE & TECHNOLOGY; AGRICULTURAL SCIENCES; Agriculture & Environment Sciences (AGE); Yemek bilimi; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Yaşam Bilimleri; Food Science; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences; Life Sciences; biobased products; offset ink; pine resin; plant-based oils; printing